2018
DOI: 10.1590/s0100-204x2018000800005
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of soybean grown in succession to winter cover crops

Abstract: The objective of this work was to evaluate the effect of winter cover crop species on the agronomic performance of soybean (Glycine max) cropped in succession, under a no-tillage system. The study was conducted during three crop seasons (2011/2012, 2012/2013, and 2013/2014), with the following cover crops: white oat (Avena sativa), black oat (Avena strigosa), ryegrass (Lolium multiflorum), vetch (Vicia sativa), forage radish (Raphanus sativus), the intercrop black oat + forage radish, and wheat (Triticum aesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
10
0
4
Order By: Relevance
“…IAC-Fava larga), Crotalaria juncea and Crotalaria spectabilis. The cover plants studied presented good potential for soil conservation, due to the permanence of residues on the surface, except for Mucuna aterrima and Crotalaria spectabilis.Soil management practices such as no-tillage (NT), crop rotation and use of cover crops are important techniques which can maintain and/or promote yield gains and soil quality with less environmental impact (Krenchinski et al, 2018;Pavinato et al, 2017). However, these techniques are not adapted to the soil and climate conditions of the Cerrado in south Piauí, with poor results for NT, especially regarding the formation of straw, which is an essential factor for the good performance of this system.…”
mentioning
confidence: 99%
“…IAC-Fava larga), Crotalaria juncea and Crotalaria spectabilis. The cover plants studied presented good potential for soil conservation, due to the permanence of residues on the surface, except for Mucuna aterrima and Crotalaria spectabilis.Soil management practices such as no-tillage (NT), crop rotation and use of cover crops are important techniques which can maintain and/or promote yield gains and soil quality with less environmental impact (Krenchinski et al, 2018;Pavinato et al, 2017). However, these techniques are not adapted to the soil and climate conditions of the Cerrado in south Piauí, with poor results for NT, especially regarding the formation of straw, which is an essential factor for the good performance of this system.…”
mentioning
confidence: 99%
“…Regarding the effect of cover plants on the economic interest ones, Lima et al (2012a), observed that when using a cover cocktail (black oat, forage turnip and common vetch) the emergence speed index of soybean seedlings was higher, providing more vigorous seedlings. With better-performing seedlings, the yield may benefit, as reported by Krenchinski et al (2018), which showed an increase in soybean (Glycine max) production when using cover cropping, pointing out the potential of the black oat and the forage turnip.…”
Section: Introductionmentioning
confidence: 80%
“…The forage radish (Raphanus sativus L.) and vetch (Vicia sativa L.) are forage species considered important for cultivation during winter in southern Brazil, especially to cover and protect soil with plants, plant residues in notillage systems, and as weed suppressors (Cutti et al, 2016;Krenchinski et al, 2018). The forage radish is mainly used due to its fast growth, low nutrient demand, high tolerance to climatic adversities, and pivotal root system, which increases soil exploration and may improve soil physical conditions, in addition to presenting an intense nutrient cycling rate, with easy availability to the crop in succession (Cardoso et al, 2014;Krenchinski et al, 2018). As for the vetch, it is widely used because of its considerable nitrogen fixation capacity and rapid availability to next crops, which is illustrated by the fact that it can provide more than 200 kg of nitrogen per hectare (Restovich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%